Arabic as A Window in Perceiving The World: A Contextualizing The Sociology of Literature - Teguh Luhuringbudi; Fitri Liza; Kuliyatun Kuliyatun; Dewi Nita Utami (TATHO: International Journal of Islamic Thought and Sciences, 2024)
In an effort to avoid the negative effects of modern globalization on the existence of a scientific discipline, such as the science of Arabic, it is important to make Arabic contribute to presenting Arabic as a medium in photographing various social phenomena of modern society. This study presents a systematic literature review on the topic of 'Arabic Language as a Window in Viewing the World.' It is based on the primary source dissertation 'Literature and Nationalism: A Study of the Poems of Mahjar 'Alī Aḥmad Bākathīr' by Minatur Rokhim (2021). The purpose of this systematic literature review (SLR) is to reconstruct the theoretical and practical understanding of Arabic as a window for viewing the world. This will be achieved by analysing the substance and principles of the dissertation. This study concludes that incorporating environmental needs and interests, both locally and nationally, can position Arabic language knowledge as an asset in promoting global unification in a scientific, applied, and commercial manner.